Editorial, The New Cities of the Twentieth Century (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The twentieth century is best known for the dramatic events that marked it. Two world wars have scanned its duration, dividing it into two, but connected by a thread of continuity. In the background of the conflict between totalitarianism and democracy it has been a century driven by common ambitions, translated in decisive, contrasting transformations in terms of conquests of economic and social rights.The twentieth century must therefore be re-read in its contradictions, in the folds of a simple mapping of the movements and ideologies. It is possible to gather the underlying reasons that led to the competition between antagonistic fronts, counterposed in claiming the primacy of change and achievements. The foundation of new cities occurred within that framework, just as the oscillations that distinguished their form reflect their dramatic diversity.